Collagenous colitis in Orebro, Sweden, an epidemiological study 1984-1993. Issue 3 (September 1995) - Bohr, J; Tysk, C; Eriksson, S; Järnerot, G
Abstract : The incidence and prevalence of collagenous colitis are unknown. An epidemiological study was undertaken between 1984-93. All patients living in the immediate catchment area of Orebro Medical Center Hospital with the diagnosis collagenous colitis were identified. Biopsy specimens classified as unspecific intestinal fibrosis were re-examined to identify cases not correctly diagnosed at first. Medical records were scrutinised and colorectal biopsy specimens re-evaluated. Thirty patients with collagenous colitis were diagnosed during the study period. The female:male ratio was 9:1. The median age at diagnosis was 64 (28-78) years. The prevalence at 31 December 1993, was 15.7/10(5) inhabitants (95% CI; 9.8 to 21.6/10(5)). The mean annual incidence during the period 1984-93 was 1.8/10(5) inhabitants (95% CI; 1.2 to 2.4/10(5)). A peak incidence was found in women 70-79 years old. Collagenous colitis occurs mainly in middle aged women, and the frequency is higher than earlier anticipated. The prevalence and incidence is similar to primary biliary cirrhosis. In women 70-79 years of age, the incidence for collagenous colitis approaches the incidence for ulcerative colitis.